The reasons for the prevention of Islamic cities In MOROCO Between the 2-3 centuries AH / 8-9 CE - صارم , وفاء; حسن , غادة; موسى , علي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
With the beginning of civil society, man began thinking about building cities, and when he faced many natural and human challenges, he started thinking about fortifying and increasing its prevention. The architects of the cities of the Arab Maghreb were able in the 2-3 centuries AH / 8-9 CE to build cities that defied these factors, so they chose for them the best natural sites that give their residents the strength and strength in addition to some human factors such as fences, castles, forts, and others. Indeed, these cities withstood their external enemies and remained so until the symptoms of disappearing appeared at the hands of those inside.